CENTELLA ASIATICA EXTRACT INCREASED ON THE LEVEL OF INTERLEUKIN 6 (IL-6) IN MICE - Kerta Besung, I Nengah; Mantik Astawa, Nyoman; Suatha, I Ketut; -, Hartaningsih (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 5, No. 1 Januari 2011)
Salmonellosis is still problem in many developing countries including Indonesia. Themain problem in controlling and handling the disease is that only few antibiotics are availableto cure the disease. In addition, the prolonged use of such antibiotics often lead to bacterialresistant against the antibiotics. A herbal drugs such as Centella asiatica (in Indonesia isknown as pegagan) contains triterphenoid saphonins which acts as immunostimulant capableof enhancing the phagocytic activity of macrophages. However, no study has been conductedto investigate the use pegagan in activating macrophage of mice infected with Salmonellatyphi. A study was therefore conducted to find out the ability of Cantella asiatica inenhancing on the level interluekine (IL)-6 following challenge with Salmonella typhi. It istherefore expected that herbal drug such as Cantella asiatica can be used as an alternativemedicine to prevent and cure salmonellosis in both animals and human.Experimental laboratory studies were conducted using Completely FactorialRandomized Design. Mice were divided into 4 groups and they were treated respectively withdestilated water (negative control), 125, 250, and 500 mg/kg bw of Centella asiatica extract.The treatment was conducted daily for 2 weeks and the mice were then inoculated with 105cells of S. typhi. The level of IL-6 response were examined 24 hours, 2 weeks, and 4 weeksafter inoculation with S. typhi.The result showed that treatment of mice with Centella asiatica extract significantly(p<0,05) enhaced IL-6 level of Balb/c mice following inoculation with S. typhi. The highestIL-6 level were observed in mice treated Centella asiatica extract at the dose of 500 mg/kgBW (385,9257±125,4314 pg/ml serum). And the highest IL-6 level were observed at 2 weeksfollowing inoculation with S. typhi (533.4262 ± 81.7184 pg / ml).A further study is recomended to examine the celluler immune response and moredetailed study on the humoral immune response of animals or human before this herbal isused as alternatif medicine to prevent and cure typhoid fever. It is also important to study thebest preparation, the half life, and the side effect of Centella asiatica in human and animals.
Keywords: pegagan, Centella asiatica, IL-6, antibody, S. typhi